HEALTH EDUCATION IN THE FRAMEWORK OF HYPERTENSION PREVENTION AND CONTROL IN THE ELDERLY - Dwi Agustina; Nur Achirda; Restu Arya Pambudi; Toto Aminoto (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
Introduction: The old population has continued to grow in recent decades, which has resulted in an increase in health problems for the aged, such as the spread of hypertension. According to the measurement results, the majority of residents of Posbindu Kenanga II have hypertension. As a result, it is necessary to provide education about hypertension at an early stage. Method: Community service activities were carried out at Posbindu Kenanga II Jatimelati Pondok Melati Bekasi in October 2023, targeting 25 older adults, all women. Activities carried out include measuring blood pressure & hypertension knowledge measurements, and health education. Results: Most of the elderly (64%) suffer from hypertension. The average knowledge before and after community service increased from 43.6 to 70.4, with a p-value of 0.001. Conclusion: Community service activities have boosted the elderly's understanding of hypertension significantly. As a result, it is essential to continue this activity on an ongoing basis by incorporating proper exercise for controlling hypertension.